Unleashing the potential of university entrepreneurship education: A mandate for a broader perspective - Donna M. De Carolis; Barrie E. Litzky (New England Journal of Entrepreneurship, 2019)
Purpose – The purpose of this paper is to highlight the ways in which traditional views of entrepreneurs and entrepreneurship have inadvertently limited entrepreneurship education. The authors propose a broader view of what it means to be an entrepreneur and describe a disruptive approach to entrepreneurship education, one that centers around building students’ entrepreneurial mindset. By tapping into students’ “inner entrepreneur” and nurturing their abilities to think and act creatively, embrace failure, effect change and be resilient, the authors are preparing them for the challenges of the twenty-first century labor market. Design/methodology/approach – This is a perspective paper about how the traditional views of entrepreneurship education may be limiting its potential to create entrepreneurial college graduates set to take on twenty-first century careers. Findings – Teaching the entrepreneurial mindset and process will allow us, as educators, to best prepare our students for the complexities of the current and future workforce. Originality/value – By embracing the original meanings of the word “entrepreneur” – an act of reaching out and capturing and undertaking – the authors demystify what it means to be an entrepreneur. When we adopt a broader and more accurate conceptualization of “the entrepreneur,” we can teach our students to be the entrepreneurs of their lives.